Transition of Acehnese Legal Culture Towards the Implementation of Qonun on Sharia Finance with Islamic Law Analysis - Khairul Azhar, Khairul (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to analyze the transition of the legal culture of the Acehnese people towards the implementation of Qanun Number 11 of 2018 concerning Islamic Financial Institutions (LKS). The implementation of this qanun is an important step in realizing a sharia-based financial system in Aceh, which has a Muslim majority population. The research method used is an inductive approach in qualitative research with the type of empirical legal research or socio-legal research, which aims to understand how the law operates in society. The three main approaches in this study are analysis of community responses, inhibiting and supporting factors, and the influence of changes in legal culture on the implementation of this qanun. The results of the study show that the implementation of the LKS Qanun received a positive response from the Acehnese people, with significant changes in legal culture, where people began to shift from conventional bank transactions to Islamic financial institutions. Support for this qanun cannot be separated from political factors, the culture of a Muslim majority society, and clear legal substance. However, there are several challenges, such as rejection from some people who feel disadvantaged, as well as limited facilities and infrastructure that are not yet fully ready. However, the changes in legal culture that have occurred have contributed to positive economic growth and the welfare of the Acehnese people. The implementation of this qanun has succeeded in becoming part of the Indonesian economic legal system and has the potential to be adapted by other regions with similar cultures. Thus, it can be concluded that the implementation of the LKS Qanun has succeeded in providing a positive impact on changing the legal culture in Aceh.